(untitled) (Journal of Information Technologies in Education (ITE), 2010)
In the publication modern research areas of information-communication technologies in pedagogical science are identified. The basic requirements of the new passport for the specialty 13.00.10 - Information and Communication Technologies in Education are described. On this specialty the defence of the degree of doctor and candidate of pedagogical science may be carried out.